Evaluation of Vaccination Training in Pharmacy Curriculum: Preparing Students for Workforce Needs - Mary Bushell; Jane Frost; Louise Deeks; Sam Kosari; Zahid Hussain; Mark Naunton (MDPI AG, 2020)
Background: To introduce and evaluate a university vaccination training program, preparing final year Bachelor of Pharmacy (BPharm) and Master of Pharmacy (MPharm) students to administer vaccinations to children and adults in community pharmacy and offsite (mobile and outreach) settings. Methods: Final year BPharm and MPharm students were trained to administer intramuscular vaccinations to adults and children. The education program embedded in pharmacy degree curriculum was congruent with the requirements of the Australian National Immunisation Education Framework. The training used a mix of pedagogies including online learning; interactive lectures; and simulation, which included augmented reality and role play. All pharmacy students completing the program in 2019 were required to carry out pre- and post-knowledge assessments. Student skill of vaccination was assessed using an objective structured clinical assessment rubric. Students were invited to complete pre and post questionnaires on confidence. The post questionnaire incorporated student evaluation of learning experience questions. Results: In both cohorts, student vaccination knowledge increased significantly after the completion of the vaccination training program; pre-intervention and post-intervention mean knowledge score (SD) of BPharm and MPharm were (14.3 ± 2.7 vs. 22.7 ± 3.3; p < 0.001) and (15.7 ± 2.9 vs. 21.4 ± 3.2; p < 0.001) respectively. There was no difference between the BPharm and MPharm in the overall knowledge test scores, (p = 0.81; p = 0.95) pre and post scores respectively. Using the OSCA rubric, all students (n = 52) were identified as competent in the skill of injection and could administer an IM deltoid injection to a child and adult mannequin. Students agreed that the training increased their self-confidence to administer injections to both children and adults. Students found value in the use of mixed reality to enhance student understanding of the anatomy of injection sites. Conclusion: The developed vaccination training program improved both student knowledge and confidence. Pharmacy students who complete such training should be able to administer vaccinations to children and adults, improving workforce capability. Mixed reality in the education of pharmacy students can be used to improve student satisfaction and enhance learning.